Penerapan Teknik Kursi Kosong dalam Konseling Gestalt untuk Meningkatkan Kepercayaan Diri Siswa - Habsy, Bakhrudin All; Putri, Evelyna Eka; Saputri, Berbella Khayla Syavanda; Novitasari, Radya Putri; Muflikhatin, Luluk (TSAQOFAH, 2024)
Gestalt counseling teaches that individuals are wholes greater than the sum of their parts. In the context of self-confidence, this means recognizing and embracing all aspects of oneself, both positive and negative, as integral parts of their being. This study aims to examine the application of the empty chair technique in Gestalt counseling to enhance students' self-confidence. Gestalt counseling is an approach that emphasizes present awareness and the individual's relationship with their environment. This study employs a qualitative method with a literature review approach, using relevant literature sources as primary data, such as research findings, research reports, and scientific journals. After gathering the data sources, a content analysis of the literature review was conducted. The results of this study indicate that the empty chair technique in Gestalt counseling is effective in improving students' self-confidence. The empty chair technique helps enhance interpersonal communication skills and reduce negative behaviors. Although Gestalt counseling has advantages in increasing self-awareness and self-confidence, it also has drawbacks such as a lack of structure in counseling sessions and unsuitability for all types of issues or client conditions.